IMPLEMENTATION OF ADDITIONAL CRIMINAL SANCTIONS IN THE FORM OF PAYMENT OF MONEY IN CRIME OF CORRUPTION IN INDONESIA (CRITICAL REVIEW OF THE PRINCIPLE OF LEGAL CERTAINTY IN DECISION NUMBER 5035 K/Pid.Sus/2022) - egiardus bana (Khairun Law Journal, 2023)
Additional criminal sanctions in the form of payment of replacement money to perpetrators of corruption are seen as strategic in the context of recovering state financial losses. The sanctions are regulated in Article 18 paragraph (1) of Law Number 31 of 1999 concerning the Eradication of Corruption Jo. Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 Law concerning Eradication of Corruption Crimes. In the application of the law, there is an imbalance regarding how additional punishment in the form of payment of replacement money should be applied to perpetrators of corruption. This results in the creation of legal uncertainty. For this reason, in order to overcome this, it is necessary to conduct a critical study regarding the application of additional criminal sanctions in the form of replacement money in Decision Number: 5035 K/Pid.Sus/2022. By conducting a critical review, it is hoped that the existence of additional criminal sanctions in the form of payment of reimbursement money can be applied consistently so as to provide legal certainty guarantees for perpetrators of corruption.